Explanation and elucidation of cancer in reference to Greco-Arabic literature - Ahmad, Wasim; Zulkifle, Mohd; Hamiduddin, -; Afreen, Sadaf; Rahman, Obaidur (Bangladesh Journal of Medical Science, 2019)
Muslim scholars made tremendous contribution in various fields of science and their benefaction of work exhibits in all branches of medicine. Cancer is discussed by then Muslim scholars like Ibn Sina, Razi , Ismail Jurjani ,Hunain b. Ishaque, Rabban Tabri, Ahmad b. Mohammad Tabri, , Ibn ul Quff, Ibn Zuhr etc. In their descriptions cancer means Sartan (crab) as it reflects the true character of disease, since it sticks to the part stubbornly like a Sartan. Galen states that Sartan is the result of an excess of black bile. It may be due to an excessive hotness and dryness of liver by which consumed foods transform into irritant morbid matter. Concurrently, the spleen becomes weak and is unable to absorb the Sawda (black bile). Muslim scholars classified and distinguished clearly among the varieties of cancer in relation to specific organs such as eye, stomach, bladder, penis, uterus, mouth, and nerve tumours. The need of the hour is to evaluate and analyse the disease along with its pathophysiology, predisposing factors, differential diagnosis, and varieties of therapeutic paradigms that include nutrition, drugs, Ishal (bowel cleansing), Tanqia (evacuation of morbid matter from the body), surgical and non surgical interventions i.e. leaching , Amal kai (cauterization). Since the cancer is spreading at an incredible rate in both developed and developing countries but no way of relief is ensured yet in any system of medicine. Greco-Arabic literature has rich potential to intervene in palliative way in such dreadful disease. Likewise, Ray born Razi asserted that when cancer is at the beginning, it can be kept stationary and can be prevented from ulceration. This systematic review highlights relevant Greco-Arabic literature on cancer. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.184-189